Strategi Pemasaran Hotel Four Points By Sheraton Medan Menggunakan Analisis SWOT - Manalu, Roulina (Politeknik Pariwisata Medan, 2025)
This study aims to identify and analyze the marketing strategies applied by Four Points by Sheraton Medan Hotel using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). This analysis is conducted to explore internal strengths, existing weaknesses, as well as external opportunities and threats influencing the hotel’s marketing performance. The results indicate that the hotel’s strengths lie in its international brand reputation, comprehensive facilities, and strategic location. However, weaknesses such as dependency on specific market segments and lack of digital innovation remain challenges. Major opportunities include the growth of domestic tourism and increasing demand for internationally standardized services. Conversely, threats emerge from intense hotel competition and global economic fluctuations. By leveraging its strengths and opportunities while anticipating weaknesses and threats, the hotel can formulate a more effective and competitive marketing strategy within the hospitality industry.